Unexpected Severe Tracheal Papilloma During Induction - Yanling Zhang; Xin Li; Ting Tan; Shuiting Zhang (Clinical Case Reports)
ABSTRACT Tracheal papilloma (TP) is an intricate disorder that poses challenges in the diagnosis, therapy, and management of airways due to its association with human papillomavirus infection. In this case report, we present a patient with an unexpectedly large tracheal papilloma detected during induction of anesthesia. The patient successfully underwent surgical resection of the tracheal papilloma. Postoperatively, the patient recovered well, with no recurrence of airway obstruction symptoms during the follow‐up period. Preoperative airway assessment was crucial in this case, enabling anticipation of potential airway difficulties, formulation of appropriate anesthetic and surgical plans, and ensuring the patient's safety during the perioperative period.